ANALYSIS ON THE USES OF GEO-SYNTHETICS TO STABILIZE SANDY SOIL SUB GRADE - Ali A. Al-Zubaidi; Rand Otbah Farqad (Journal for Technology and Science, 2026)
Objective: The main goal of this study is to compare how well synthetic and natural geo-textiles work to stabilise sub-grade soil. Method: This study looks at what happens when geo-textiles are used to strengthen the soil under a building. In the lab, the load-penetration abilities of granular soils that had been strengthened with geo-textiles were tested using California bearing ratio (CBR) tests. Results: By using geotextiles, the soil's ability to hold water can be fixed. Geosynthetics are often used to improve road pavement, among other things. Novelty: Soil stabilisation methods include stabilising the soil with cement, lime, hydrocarbons, chemicals, and the new and promising method of stabilising the soil with Geo textiles and Geo artificial fibres.